Cetacean strandings in San Diego County, California, USA: 1851–2008 - Danil , Kerri; Chivers , Susan J.; Henshaw , Mike D.; Thieleking , Janet L.; Daniels , Risa; St. Leger , Judy A. (J. Cetacean Res. Manage., 2023)
There were 717 cetacean strandings recorded in San Diego County, California, USA between 1851 and 2008. These strandings comprised 18 odontocete and 6 mysticete species. Common dolphins (both the short-beaked (Delphinus delphis) and long-beaked common dolphin (D. capensis)) were the most commonly stranded cetacean species (43.2%), followed by bottlenose dolphins (Tursiops truncatus) (16.5%), gray whales (Eschrictius robustus) (11.0%), and Pacific white-sided dolphins (Lagenorhyncus obliquidens) (7.0%). A higher number of strandings was observed in the La Jolla and Coronado/Imperial Beach areas, which likely reflects the influence of coastal protrusions in those regions. Strandings of bottlenose dolphin neonates suggests their calving season extends from May to September. Strandings of common dolphin species peaked in the early- to mid-1970s and in the late-1990s to 2008, coincident with cool oceanographic regimes. In addition, extralimital strandings of harbour porpoises and temporal changes in stranding rates of Dall’s porpoises (Phocoenoides dalli) and short-finned pilot whales (Globicephala macrorhynchus) may have been associated with changes in oceanographic conditions. Evidence of human interaction in strandings included entanglements, boat strikes, shootings and harpooning. Overall, the stranding record largely reflected the species composition of the Southern California Bight and provided confirmation for presence of cryptic species not previously recorded by aerial and ship surveys.